THE MEDIATING ROLE OF ENTREPRENEURIAL ATTITUDE ON THE EFFECT OF PROPENSITY TO TAKE RISKS ON ENTREPRENEURIAL INTENTION BY USING FAMILY'S BACKGROUND AS A CONTROL VARIABLE - Dude, Susana Avila; Mulyadi, Hari; Kurjono (Jurnal Pendidikan Ilmu Sosial, 2024)
This study aims to determine the mediating role of entrepreneurial attitudes on the relationship between risk-taking tendencies and entrepreneurial intentions by using family's background as a control variable. The theory used is the Theory of Planned Behavior (TPB). The population amounted to 244 students so that the sample size used amounted to 152 students of economic education at the Universitas Pendidikan Indonesia. Data collection using a questionnaire. The data analysis technique uses Structural Equation Modeling (SEM) with Smart PLS 3 because Smart PLS 3 can measure a small population. The results showed that the tendency to take risks has no effect on entrepreneurial intentions, the tendency to take risks has a positive and significant effect on entrepreneurial attitudes, entrepreneurial attitudes have no effect on entrepreneurial intentions, entrepreneurial attitudes do not mediate the effect of risk-taking tendencies on entrepreneurial intentions, and there are no significant differences in entrepreneurial intentions in terms offamily background.